Regulate us, please!: On strategic lobbying in Cournot-nash oligopoly - Peter Michaelis (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1994)
Empirical studies on industry lobbying sometimes reveal that certain firms within an industry behave atypically in that they promote cost driving regulations like, e.g., environmental standards. For analysing this phenomenon of 'strategic lobbying1, the present paper combines a heterogeneous Cournot-Nash oligopoly with a model of endogenous policy making where two parties compete for campaign contributions spent by the regulated industry. It is shown that the existence of potential regulation gains (and consequently the incentive for strategic lobbying activities) depends on the relationship between possible cost differentials and the market structure of the industry under consideration. Based on these results, the paper examines the effects of strategic lobbying for two different scenarios. The first scenario assumes that only one firm is engaged in lobbying, whereas the second scenario looks at simultaneous (competing) lobbying activities by several firms.
Keywords: 330